Coordinating DNA replication initiation with cell growth: differential roles for DnaA and SeqA proteins. - Boye, E (1996)
We describe here the development of a new approach to the analysis of Escherichia coli replication control. Cells were grown at low growth rates, in which case the bacterial cell cycle approximates that of eukaryotic cells with G1, S, and G2 phases: cell division is followed sequentially by a gap period without DNA replication, replication of the single chromosome, another gap period, and finally the next cell division. Flow cytometry of such slowly growing cells reveals the timing of replication initiation as a function of cell mass. The data show that initiation is normally coupled to cell physiology extremely tightly: the distribution of individual cell masses at the time of initiation in wild-type cells is very narrow, with a coefficient of variation of less than 9%. Furthermore, a comparison between wild-type and seqA mutant cells shows that initiation occurs at a 10-20% lower mass in the seqA mutant, providing direct evidence that SeqA is a bona fide negative regulator of replication initiation. In dnaA (Ts) mutants the opposite is found: the mass at initiation is dramatically increased and the variability in cell mass at initiation is much higher than that for wild-type cells. In contrast to wild-type and dnaA(Ts) cells, seqA mutant cells frequently go through two initiation events per cell division cycle, and all the origins present in each cell are not initiated in synchrony. The implications for the complex interplay amongst growth, cell division, and DNA replication are discussed.